Applicability of mesopic factors to the driving task. (February 2016) - Gibbons, RB; Terry, T; Bhagavathula, R; Meyer, J; Lewis, A
With the advent of light-emitting diode technology being applied to roadway lighting, the spectral power distribution of the light source is becoming much more important. In this experiment, the detection of pedestrians at five adaptation levels under three light sources, high pressure sodium and light emitting diodes of two colour temperatures was measured in realistic roadway scenarios. The results show that while the light source type was not significant, an increase in adaptation luminance increased the detection distance. As the offset of the object to the roadway increased, some spectral effects became more significant; however, this effect was not consistent across all angles of eccentricity. The conclusions from this work indicate that mesopic factors may not be applicable on high-speed roads.